Diskresi Perekrutan PPNPN (PEGAWAI PEMERINTAH NON PEGAWAI NEGERI) Berdasarkan Surat Menteri PANRB NO. B/185/M.SM.02.03/2022 Tentang Status Kepegawaian Di Instansi Pemerintah Pusat Serta Pemerintah Daerah - Duwi Astuti; Aris Toening Winarni (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
This change in regulations regarding employment status creates new dynamics in the implementation of employee recruitment in various government agencies. This creates challenges in maintaining the quality and integrity of the state civil apparatus, along with efforts to increase the professionalism and effectiveness of the bureaucracy. To understand the impact of this change comprehensively, it is necessary to conduct in-depth research that can provide better insight into how the PPNPN recruitment discretion can influence the letter of the Minister of PANRB No. B/185/M.SM.02. 03/2022 concerning Employment Status in Central Government and Regional Government institutions, the contents of which are that honorary employees will completely expire on November 28 2023 and be replaced by PPPK. This regulation means that government officials no longer have discretionary authority to appoint honorary employees or PPNPN. Flexibility of authority for the government to meet the needs of supporting personnel through outsourcing mechanisms. Document Study research method: by reviewing existing related documents. The documentation study approach is research that analyzes the PANRB Minister's Letter and other related policy documents to understand the content, objectives and provisions of the regulations. Data collection through literature and qualitative analysis. The research results show that violations of the PANRB ministerial regulations will be subject to sanctions in accordance with the provisions of the regulations. To meet the shortage of ASN positions or other supporting staff, the leadership proposed the formation of CPNS and PPPK after mapping the positions. The recommendations from this research are the importance of the availability of human resources for civil servants for good public services, and changes in policy regarding the recruitment of honorary employees by the government or leadership.